2021
DOI: 10.7717/peerj.11386
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic communities from a lava tube cave in La Palma Island (Spain) are involved in the biogeochemical cycle of major elements

Abstract: Lava caves differ from karstic caves in their genesis and mineral composition. Subsurface microbiology of lava tube caves in Canary Islands, a volcanic archipelago in the Atlantic Ocean, is largely unknown. We have focused the investigation in a representative lava tube cave, Fuente de la Canaria Cave, in La Palma Island, Spain, which presents different types of speleothems and colored microbial mats. Four samples collected in this cave were studied using DNA next-generation sequencing and field emission scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 101 publications
4
36
0
Order By: Relevance
“…Our results were consistent with previous moonmilk microbiome studies where Actinobacteria represented a high percentage of the moonmilk bacterial community (Maciejewska et al, 2018;Park et al, 2020). To the best of our knowledge, there is no study associating Crossiella relative abundance with moonmilk formation, except in the study on a volcanic cave where Crossiella relative abundance was 2.5% (Gonzalez-Pimentel et al, 2021). However, a few authors reported the finding of Crossiella not only in carbonate environments such as weathered rock caves (Ma et al, 2021), but also in deteriorated stone monuments (Li et al, 2018).…”
Section: Bacterial Communities On Cave Formations: From Sediments To ...supporting
confidence: 91%
See 1 more Smart Citation
“…Our results were consistent with previous moonmilk microbiome studies where Actinobacteria represented a high percentage of the moonmilk bacterial community (Maciejewska et al, 2018;Park et al, 2020). To the best of our knowledge, there is no study associating Crossiella relative abundance with moonmilk formation, except in the study on a volcanic cave where Crossiella relative abundance was 2.5% (Gonzalez-Pimentel et al, 2021). However, a few authors reported the finding of Crossiella not only in carbonate environments such as weathered rock caves (Ma et al, 2021), but also in deteriorated stone monuments (Li et al, 2018).…”
Section: Bacterial Communities On Cave Formations: From Sediments To ...supporting
confidence: 91%
“…Moonmilk deposits are the best known and widespread example of microbially-induced calcium carbonate precipitation (MICP) in different subterranean environments, from karstic (Cañaveras et al, 2006) and volcanic caves (Gonzalez-Pimentel et al, 2021) to granite tunnels (Miller et al, 2018). In fact, a growing research interest has recently been raised in the scientific community on understanding microbial communities and mechanisms involved in mineral precipitation processes (Maciejewska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Strains MZ03-37 T and MZ03-48 were isolated on nutrient agar (NA, BD, Sparks, USA) with 3% of magnesium sulfate and 2% of glycerol at 28°C for 21 days, from two different locations in the lava tube Fuente de la Canaria (latitude: 28°35'25.2“N and longitude: 17°48′01.3”W) located in La Palma Island, Canary Islands (Spain) (Gonzalez-Pimentel et al, 2021 ). MZ03-37 T was isolated from a light-brown mucolite and MZ03-48 from a dark-brown microbial mat, both sampling sites separated by a distance of 15 m. Morphological, chemotaxonomical, and physiological studies were carried out from cultures on yeast extract-malt extract agar (International Streptomyces Project medium no 2, ISP2) at 28°C, except when otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…The company MicrobesNG (Birmingham, UK) was responsible for sequencing genomic DNA in order to assemble the draft genome for both bacteria. Sequencing of genomic DNA of strains MZ03-37 T , MZ03-48, and Streptomyces palmae CMU-AB204 T and subsequent assembly was described by Gonzalez-Pimentel et al ( 2021 ). The genome of Streptomyces ramulosus NRRL B-2714 T was assembled following the same procedure using the raw data (Ju et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…An interesting aspect emerging from our microbiological investigation is the scarce contribution of Archaea to microbial communities. Most of the microbial communities of caves, located in different geographical regions and environmental conditions, showed an almost exclusive dominance of Bacteria and a negligible percentage of Archaea (Pasic et al, 2010;Itcus et al, 2018;Wiseschart et al, 2019;Jurado et al, 2020;Gonzalez-Pimentel et al, 2021). Only in a few cases, Archaea were linked to MnFe deposits, such as in Lechuguilla Cave (Northup et al, 2003).…”
Section: Mineralogical and Microbiological Implicationsmentioning
confidence: 99%